Upaya Menumbuhkan Budaya Literasi Peserta Didik Melalui Penerapan Metode Retelling dalam Pembelajaran SKI - Maunah, Alil (Pascasarjana IAIN Kudus, 2022)
Growing up Student Literacy Culture Through the Application of the Retelling Method in SKI Learning.The purpose of this study was to find out the application of the retelling method in learning Islamic Cultural History and to find out the efforts of teachers in cultivating a reading literacy culture in students at MTsN 2 Kudus. The lack of interest in reading, especially among students, is a problem that needs to be found a solution, then the application of the retelling method is an alternative strategy in fostering a literacy culture of students in madrasas. This type of research uses a descriptive qualitative approach with data collection techniques using observation, interviews, and documentation. The results showed that the application of the retelling method in learning Islamic Cultural History at MTsN 2 Kudus had been carried out quite effectively as an effort to foster a culture of literacy in students. Through this retelling method, students hone their ability to understand Islamic Cultural History material, communicate in the form of retelling Islamic Cultural History material that has been studied using their own language, where this ability is one aspect of literacy. Tujuan penelitian ini untuk mengetahui penerapan metode retelling dalam pembelajaran SKI dan mengetahui upaya guru dalam menumbuhkan budaya literasi membaca pada peserta didik di MTs Negeri 2 Kudus. Minimnya minat membaca terutama di kalangan peserta didik menjadi persoalan yang patut ditemukan solusinya, maka penerapan metode retelling menjadi alternatif strategi dalam menumbuhkan budaya literasi peserta didik di madrasah. Jenis penelitian ini menggunakan pendekatan kualitatif deskriptif denganteknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi.Hasil penelitian menunjukkan bahwa penerapan metode retelling dalam pembelajaran SKI di MTs Negeri 2 Kudus sudah terlaksana cukup efektif sebagai salah satu upaya untuk menumbuhkan budaya literasi peserta didik. Melalui metode retelling tersebut, peserta didik terasah kemampuan dalam memahami materi SKI, mengkomunikasikan dalam bentuk menceritakan kembali materi SKI yang telah dipelajari dengan menggunakan bahasanya sendiri, dimana kemampuan ini merupakan salah satu aspek dalam literasi.